Merawat Ikatan Emosional di Tanah Matrilineal: Studi Psikologi Indigenous tentang Kedekatan Ibu dan Anak Minangkabau - Putri, Dini Dwinanda; Rizki Setiawan (CV. ULIL ALBAB CORP, 2026)
This study explores the emotional closeness between mothers and children in Minangkabau society, which is shaped by a matrilineal kinship system and strong cultural values. The research aims to describe and analyze the meaning and dynamics of mother-child closeness from an indigenous psychology perspective. Employing a qualitative approach with a contextual reflective method, data were collected from 103 Minangkabau participants aged up to 27 years using open-ended questionnaires. The researcher served as the main instrument, and thematic analysis was applied to identify key patterns in responses. Results show that mothers play a central role in nurturing, transmitting cultural values, and fostering emotional bonds, with most participants reporting a very close relationship with their mothers. The study concludes that mother-child closeness in Minangkabau is deeply rooted in cultural traditions and remains resilient despite social changes.